Cell-free DNA measurement of three genomes after allogeneic MSC therapy in kidney transplant recipients indicates early cell death of infused MSC - Dreyer, Geertje J.; Drabbels, Jos JM.; de Fijter, Johan W.; van Kooten, Cees; Reinders, Marlies EJ.; Heidt, Sebastiaan (Frontiers in Immunology, 2023)
Introduction Mesenchymal stromal cell (MSC) therapy is a promising treatment that allows for drug minimization in clinical kidney transplantation. While it is thought that MSCs rapidly go into apoptosis after infusion, clinical evidence for this is scarce since methods to detect cell death of infused cells in vivo are lacking. Cell-free DNA (cfDNA) has recently gained attention as a biomarker for cell death. Methods In this study, we longitudinally measured cfDNA in plasma samples of the recipient, kidney donor, and allogeneic third-party MSC in the context of the Neptune study. cfDNA levels were measured at several time points before and after allogeneic MSC infusion in the 10 recipients who participated in the Neptune study. cfDNA ratios between the recipient, kidney graft, and MSC were determined. Results We observed a peak in MSC-derived cfDNA 4 h after the first and second infusions, after which MSC-derived cfDNA became undetectable. Generally, kidney graft-derived cfDNA remained in the baseline-level range. Discussion Our results support preclinical data that MSC are short-lived after infusion, also in a clinical in vivo setting, and are relevant for further research into the mechanism of action of MSC therapy.